Carbon emission effects of land use change in Nanchang, West of Central China Region - Shuai Fu; Bingxian Xu; Yuxin Peng; Ciyi Huangxiong; Xiuxiang Li (Scientific Reports)
Abstract Urban development leads to frequent changes in land use, which leads to temporal and spatial variation of carbon emissions. In this study, land use change data, economic and social data, and energy consumption data of Nanchang City from 2000 to 2020 were used to estimate the spatio-temporal evolution of carbon emissions in Nanchang City, and the LMDI model was used to identify the main driving factors affecting the change of carbon emissions in Nanchang City. It is found that from 2000 to 2020, the carbon emission of Nanchang City has a great change, showing a “parabolic” change law, that is, rising first and then decreasing. Comparing the carbon emissions of various districts and counties, the central city is higher than the surrounding districts and counties. Economic development, land use activities and population status have a positive effect on the increase of carbon emissions, and carbon emission intensity per unit of land and land intensity per unit of GDP have a positive effect on the reduction of carbon emissions. The adjustment and optimization of energy consumption structure and the improvement of human-land policies in Nanchang from the perspectives of optimizing land use layout and structure, rationally controlling population size, and advocating low-carbon lifestyle are conducive to the construction of ecological civilization and sustainable development of Nanchang.